2014
DOI: 10.1007/s10620-014-3436-4
|View full text |Cite
|
Sign up to set email alerts
|

Low-FODMAP Diet for Irritable Bowel Syndrome: Is It Ready for Prime Time?

Abstract: Irritable bowel syndrome (IBS) is a chronic gastrointestinal disease, which adversely affects the quality of life. Its prevalence has been reported to be around 10-15 % in North America and constitutes the most common cause for gastroenterology referral. Unfortunately, the pathophysiology of IBS is not completely understood. Not surprisingly, the management strategies can leave the patients with inadequate symptom control, making IBS a debilitating gastrointestinal syndrome. Dietary interventions as a treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 58 publications
0
35
0
1
Order By: Relevance
“…Not only do the symptoms overlap, but also both conditions may respond to the same dietary management strategies. Adopting a gluten-free diet typically improves celiac disease related symptoms, but it is not possible to differentiate the effects of gluten withdrawal from changes in fiber intake[20] and/or FODMAP ingestion[21,22] associated with this intervention. The latter two interventions may have significant therapeutic benefit in IBS and future studies should include detailed information regarding intake of these dietary constituents.…”
Section: Discussionmentioning
confidence: 99%
“…Not only do the symptoms overlap, but also both conditions may respond to the same dietary management strategies. Adopting a gluten-free diet typically improves celiac disease related symptoms, but it is not possible to differentiate the effects of gluten withdrawal from changes in fiber intake[20] and/or FODMAP ingestion[21,22] associated with this intervention. The latter two interventions may have significant therapeutic benefit in IBS and future studies should include detailed information regarding intake of these dietary constituents.…”
Section: Discussionmentioning
confidence: 99%
“…FODMAPs can exacerbate IBS symptoms through various mechanisms [20,21] . First, FODMAPs are poorly absorbed in the small bowel and they are osmotically active molecules.…”
Section: Action Mechanisms Of Fodmapsmentioning
confidence: 99%
“…First, FODMAPs are poorly absorbed in the small bowel and they are osmotically active molecules. [20,21] Several studies revealed that FODMAP-rich diet led to higher effluent wet weight resulting from increased water content. This finding has been confirmed in studies using MRI to measure small intestinal water volumes following ingestion of some FODMAPs.…”
Section: Action Mechanisms Of Fodmapsmentioning
confidence: 99%
“…With regard to different dietary interventions that have been assessed, their effectiveness has not been conclusively corroborated in spite of being a readily accessible and easy to implement option, which makes their use feasible in all healthcare centers, either alone or in combination with other measures for the reduction of this toxicity [17][18][19][20] . Based on the lack of conclusive evidence on GI toxicity reduction with nutritional interventions using the modification of a single dietary element in radiotherapy treated patients, the advantage of the low fructose, fermentable oligosaccharides, disaccharides, monosaccharides and polyols (FODMAP) diet lies in its intervention on multiple factors that influence radiation-induced enteropathy such as vowel motility regulation, lactose and osmotic agents restriction, and bacterial flora modification 9,21,22 , together with an improvement observed in abdominal symptoms of patients with inflammatory bowel disease, which has similarities with radiation-induced damage in its pathogenesis, and reported high compliance [23][24][25][26][27] . This is why assessment of this type of nutritional intervention is necessary in EBRT-treated patients in order to improve treatment tolerance and in this way positively influence patients' oncologic outcomes and quality of life.…”
Section: Introductionmentioning
confidence: 99%